2022
DOI: 10.1039/d2nr03587a
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal linear dichroism transition in two-dimensional PdPS

Abstract: The linear dichroism (LD) conversion shows promising applications for wavelength-selective photodetection. However, polarity reversal behavior of LD materials alway occurs at a certain wavelength, which can only distinguish two wavelength...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…For instance, the detector based on BP shows uniform photocurrents in the wide band range of 400 to 1700 nm . Different from the traditional photodetectors above, spectrally selective polarization photodetector can provide a dynamically adjustable response with the change of the incident wavelength of the light, which will have a good application prospect in future miniaturized and integrated LPL detection. Linear dichroic (LD) conversion, which appears as a reversal of anisotropic absorption signals on the absorption spectrum, has been shown to achieve such wavelength-selective photodetectors. However, few cases have been reported so far and all of them are inorganic systems, such as BaTiS 3 , GeAs, and PdPS . The practical application of these inorganic compounds often suffers from high cost, a complicated preparation process, and complex equipment integration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the detector based on BP shows uniform photocurrents in the wide band range of 400 to 1700 nm . Different from the traditional photodetectors above, spectrally selective polarization photodetector can provide a dynamically adjustable response with the change of the incident wavelength of the light, which will have a good application prospect in future miniaturized and integrated LPL detection. Linear dichroic (LD) conversion, which appears as a reversal of anisotropic absorption signals on the absorption spectrum, has been shown to achieve such wavelength-selective photodetectors. However, few cases have been reported so far and all of them are inorganic systems, such as BaTiS 3 , GeAs, and PdPS . The practical application of these inorganic compounds often suffers from high cost, a complicated preparation process, and complex equipment integration.…”
mentioning
confidence: 99%
“…17−20 However, few cases have been reported so far and all of them are inorganic systems, such as BaTiS 3 , 18 GeAs, 17 and PdPS. 19 The practical application of these inorganic compounds often suffers from high cost, a complicated preparation process, and complex equipment integration. With the increasing demand for LPL detection, it is urgent to explore new LD conversion materials for spectrally selective LPL detectors to meet future applications of highintegrated optical detection.…”
mentioning
confidence: 99%
“…Figure 5(d) summarizes the wavelength range and the anisotropic ratio of previously reported polarization sensitive photodetectors built of various nanowire and nanobelt materials. [45][46][47][48][49][50][51][52][53][54][55][56] It is found that the PdBr 2 nanowire photodetector exhibits the optimal anisotropic optoelectronic performance at the near-ultraviolet (405 nm) region. The remarkable polarization-sensitive performance of the PdBr 2 nanowire photodetector holds great promise for designing multifunctional optoelectronic devices and facilitating their integration and miniaturization.…”
Section: Comparisons Of Two Kinds Of Dichroism Ratio Modes (Red Linementioning
confidence: 99%
“…When unpolarized light interacts with certain materials or passes through certain filters, its electric field vibrations align predominantly in one direction, resulting in linear polarization. 2D materials with an in-plane anisotropic nature always have an LPL response. 2D layered perovskites exhibit distinct anisotropic features in both the in-plane and out-of-plane directions due to their inherent quantum well structure, making them promising candidates for LPL response. Two LPL detection mechanisms based on out-of-plane structural anisotropy (Figure a) and in-plane polarization (Figure b) are identified. In the former, maximum photocurrent occurs when the polarization plane aligns parallel to the 2D inorganic layer, while perpendicular alignment results in a minimum photocurrent.…”
Section: Lpl Detectionmentioning
confidence: 99%